NEW APPROACHES TO TEACHING OF PATHOMORPHOLOGY AND BIOPSY-AUTOPSY COURSE IN THE CONDITIONS OF MEDICAL EDUCATION MODERNISATION - Вернигородський, С.В. (World of Medicine and Biology, 2015)
The article is devoted to new approaches to improving teaching of Pathomorphology (PF) and Biopsy-Autopsy Course (BAC). The principles of teaching of PF and BAC at the department of pathological anatomy were summarized. The some mistakes in cooperation of clinicians with pathology service were analyzed. The integration of teaching, research and practice activity of medical universities and medical institutions with the creation of educational, scientific and practical associations to improve the quality of PF and BAC teaching.
Keywords: pathomorphology; biopsy-autopsy course; medical education; modernization